Patients’ perceptions on the impact of coffee consumption in inflammatory bowel disease: friend or foe? – a patient survey - Barthel, Christiane (Nutr J, 2015)
BACKGROUND: Environmental factors are an integral component in the pathogenesis of inflammatory bowel disease (IBD). There is an increasing interest in nutritive components. While the potential disease-modifying role of coffee has been intensively investigated in a variety of gastrointestinal diseases, the data on the potential impact on IBD is very limited. We aimed to determine the patients’ perspective on coffee consumption in IBD. METHODS: We conducted a questionnaire among IBD patients in Switzerland, assessing key questions regarding coffee consumption. Descriptive statistics including chi square testing were used for analysis of questionnaire data. RESULTS: Among a total of 442 patients 73 % regularly consume coffee. 96 % of patients attributing a positive and 91 % of patients attributing no impact of coffee intake on IBD regularly drink coffee and surprisingly even 49 % of those patients that assign a negative impact on disease symptoms. Among those patients refraining from regular coffee intake 62 % are convinced that coffee adversely influences intestinal symptoms, significantly more in Crohn’s disease (CD) than in ulcerative colitis (UC) (76 % vs. 44 %, p = 0.002). In total, 38 % of all study subjects suppose that coffee has an effect on their symptoms of disease, significantly more in CD (54 %) compared to UC patients (22 %, p < 0.001). Moreover, while 45 % of CD patients feel that coffee has a detrimental influence, only 20 % of UC patients share this impression (p < 0.001). CONCLUSION: Two thirds of IBD patients regularly consume coffee. More than twice as many CD compared to UC patients attribute a symptom-modifying effect of coffee consumption, the majority a detrimental one. However, this negative perception does not result in abstinence from coffee consumption. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12937-015-0070-8) contains supplementary material, which is available to authorized users.